2019
DOI: 10.1007/s00425-019-03322-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesocotyl elongation, an essential trait for dry-seeded rice (Oryza sativa L.): a review of physiological and genetic basis

Abstract: Main conclusions (1) Mesocotyl elongation is responsive to abiotic stresses, such as deep sowing drought, submergence, chilling, and salinity. (2) Humus soil culture with a burial depth of 6 cm and at the temperature of 30 °C could be the optimum method for mesocotyl length phenotyping, The frequently colocalized quantitative trait loci (QTL) controlling mesocotyl elongation were located on chromosome (3) 1 (RM562-RG146), chromosome 2 (RZ288-RM145), and chromosome 3 (RM426-RM520).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 80 publications
1
44
0
Order By: Relevance
“…The embryo proper contains the root meristem (RAM) and the shoot meristem (SAM), relevant during the vegetative and reproductive phases for the development of the plant; these consist of a pool of stem cells that divide to give rise to more daughter cells that undergo cell division and differentiation throughout the entire life of the plant ( Figure 2 ). The roots and mesocotyl continue to grow using a combination of cell division in the meristems and cell elongation in subapical regions named elongation zones, which are highly controlled by several mechanisms [ 16 , 58 , 59 , 60 , 61 ].…”
Section: Maize ( Zea Mays L)mentioning
confidence: 99%
See 1 more Smart Citation
“…The embryo proper contains the root meristem (RAM) and the shoot meristem (SAM), relevant during the vegetative and reproductive phases for the development of the plant; these consist of a pool of stem cells that divide to give rise to more daughter cells that undergo cell division and differentiation throughout the entire life of the plant ( Figure 2 ). The roots and mesocotyl continue to grow using a combination of cell division in the meristems and cell elongation in subapical regions named elongation zones, which are highly controlled by several mechanisms [ 16 , 58 , 59 , 60 , 61 ].…”
Section: Maize ( Zea Mays L)mentioning
confidence: 99%
“…These agronomic characteristics have been more studied in rice, where it has been observed that higher yield often showed a direct association with seedling vigor and establishment. Accordingly, it has been used in rice breeding programs [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mesocotyl is a structure that separates the cotyledon from the coleoptile of rice seedlings. Varieties with longer mesocotyls have increased seedling emergence vigor, making direct seeding feasible (Zhan et al, 2020). Wild rice and many ancient landraces have a long mesocotyl phenotype when germinated in deep soil or in darkness.…”
Section: Introductionmentioning
confidence: 99%
“…Transplanting and direct seeding are two major rice planting patterns. Direct seeding refers to the process of establishing seedlings into puddled or submerged soil without the transplanting process (Kumar and Ladha, 2011;Zhan et al, 2020). Compared with traditional rice transplanting, direct seeding is water-efficient and labor-saving (Kato and Katsura, 2014;Liu et al, 2015;Ohno et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, direct seeding is also facing problems such as low seedling emergence rate, poor seedling establishment, weed infestation, and high crop lodging rate ( Mahender et al, 2015 ; Lee et al, 2017 ). Mesocotyl, an organ between the coleoptile node and the basal part of the seminal root in rice seedlings, plays a key role in pushing buds out of deep water or soil for successful seedling establishment during germination ( Zhan et al, 2020 ). Thus, varieties with longer mesocotyl can be used to partially overcome the problems faced by direct seeding ( Lee et al, 2017 ; Zhan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%